Grammatical Renewal In The Thought Of Abdul Qaher Al- Jurjani And Its Impact On Modern Linguistic Studies/ التجديد النحوي عند عبد القاهر الجرجاني وأثره في الدرس اللساني الحديث - Rasheed Abdullah Al Rubaysh (Ijaz Arabi Journal of Arabic Learning, 2025)
This research aims to highlight the efforts of Imam Abdul Qaher Al-Jurjani in renewing Arabic grammar and clarifying his position on grammar and grammarians, as well as the position of modern linguists on him and his new ideas. The importance of this research stems from the position of the theory of organization in grammatical and linguistic studies and the value of Abdul Qaher Al-Jurjani's efforts in grammatical renewal through his pioneering theory, which was the result of his unique genius and critical personality. It is also important to reveal the roots of his pioneering theory, its relationship with grammar and grammarians, and its impact on those who came after him. The conclusion of this research is to present the most important results that despite the abundance of studies on Abdul Qaher Al-Jurjani from various perspectives and trends, there is still a scarcity of research on the manifestations of grammatical renewal in his thought. Among the most prominent studies on this topic are Renewalist Trends in Grammatical Studies in the Thought of Abdul Qaher Al-Jurjani and Ibn Khaldun by Dr Abdullah Al-Khathran and Renewal in the Thought of Abdul Qaher Al-Jurjani through the theory of organization.